Bulky lymph node resection in patients with recurrent epithelial ovarian cancer: impact of surgery. Issue 6 (1st October 2007) - Benedetti Panici, P; Perniola, G.; Angioli, R.; Zullo, M. A.; Manci, N.; Palaia, I.; Bellati, F.; Plotti, F.; Calcagno, M.; Basile, S.
Abstract : The aim of this study was to evaluate the role of systematic lymphadenectomy, feasibility, complications rate, and outcome in epithelial ovarian cancer (EOC) patients with recurrent bulky lymph node disease. A prospective observational study of EOC patients with pelvic/aortic lymph node relapse was conducted between January 1995 and June 2005. After a clinical and laparoscopic staging, secondary cytoreduction, including systematic lymphadenectomy, were performed. The eligibility criteria were as follows: disease-free interval ≥6 months, radiographic finding suggestive of bulky lymph node recurrence, and patients' consent to be treated with chemotherapy. Forty-eight EOC patients with lymph node relapse were recruited. Twenty-nine patients were amenable to cytoreductive surgery. Postoperatively, all patients received adjuvant treatment. The median numbers of resected aortic and pelvic nodes were 15 (2–32) and 17 (8–47), respectively. The median numbers of resected aortic and pelvic positive lymph nodes were 4 (1–18) and 3 (1–17), respectively. The mean size of bulky nodes was 3.3 cm. Four patients (14%) experienced one severe complication. No treatment-related deaths were observed. After a median follow-up of 26 months, among cytoreduced patients, 18 women were alive with no evidence of disease, nine were alive with disease. Among the 11 patients not amenable to surgery, five women were alive with persistent disease, six patients died of disease, at a median follow-up of 18 months. Estimated 5-year overall survival and disease-free interval for operated women were 87% and 31%, respectively. In conclusion, patients with bulky lymph node relapse can benefit from systematic lymphadenectomy in terms of survival. The procedure is feasible with an acceptable morbidity rate